The Influence of the Decision of the Honorary Council of Election Organizer on the Process of Selecting President and Vice President Candidates - Hidayat Romadhoni, Muhammad Hendi; Lisa, Rima April; Aviansyah, Dhifa Rifky; Aziz, Warit (Trunojoyo Madura University, 2024)
The main component of the main pillar of every democratic system is the existence of a mechanism for regularly channeling people's opinions using general elections which are held periodically. Code of Ethics is necessary to regulate the behavior and principles that must be followed by election participants. The Election Organizer Honorary Council has the function of examining alleged violations of the election organizer code of ethics, which regulated in DKPP Regulation Number 2 of 2017. This research used a normative method, that is to find legal rules, legal principles, and legal doctrines in order to answer the legal issues being faced. The approach used in this research uses a case and conceptual approach that is Case Approach. In DKPP Decision Number 135-PKE-DKPP/XII/2023, Number 136-PKE-DKPP/XII/2023, Number 137-PKE-DKPP/XII/2023, and Number 141-PKE-DKPP/XII/2023, DKPP decided to granted the complainants' complaints in part. In this decision, the Chairman of the KPU and 6 (six) KPU members were given strict warning sanctions starting from the time the sanctions were read out and ordered Bawaslu to supervise the implementation of the decision from the DKPP.